2008
DOI: 10.1007/s10344-008-0199-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence supplementary feeding on bark browsing by red deer (Cervus elaphus) under experimental conditions

Abstract: The effect of various supplementary feeds on bark browsing was studied in red deer under controlled conditions. Fifteen female red deer were randomly assigned to five dietary treatments (n=3 animals each)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
0
24
0
4
Order By: Relevance
“…In studies on red deer, animals having access to meadow hay as a sole supplementary feed consumed several times larger quantities of spruce bark than deer fed with a combination of silage, oat, and pellet concentrate (Rajský et al, 2008). In BPF meadow hay and silage (occasionally beetroots) are the main feed delivered to the bison.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on red deer, animals having access to meadow hay as a sole supplementary feed consumed several times larger quantities of spruce bark than deer fed with a combination of silage, oat, and pellet concentrate (Rajský et al, 2008). In BPF meadow hay and silage (occasionally beetroots) are the main feed delivered to the bison.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between the responses elicited in wild herbivores to predators and to non-predatory human disturbance have led to the assumption that animals may perceive all human disturbance as a predation risk (Frid and Dill 2002) and, as such, human disturbance could have important effects on habitat selection and diet composition (Lima and Dill 1990;Frid and Dill 2002). Indeed, daytime browsing of tree bark by red deer has been associated with disturbance in areas where hunting is practised, posing an increasing threat to forests (Rajsky et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors even consider this practice as negative, causing substantial browsing deterioration in forests (Luccarini et al 2006). But feeding experiments under controlled conditions (Rajsky et al 2008) indicate that correctly designed supplementary winter feeding could be used as a tool for effective game damage control. However, data in this study confirmed that migration is a very important component of resilient and sustainable ecosystems and its understanding is the key to a future successful management.…”
Section: ♂ Migrantmentioning
confidence: 99%